Penerapan Five Basic Principles of Citizen Journalism Pada Media dalam Jaringan - Manap, Abdul; AS, Enjang; Muslim, Acep (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2021)
This study aims to determine the application of five basic principles of citizen journalism in Ayobandung.com include Accuracy, Thoroughness, Transparency, Fairness, and Independence. This research uses the paradigm of constructivism with a qualitative approach, and descriptive methods.The results showed that it apply the five basic principles of the Five Basic Principles of Citizen Journalism as an accountability to netizens' writings, so that they are feasible and safe for public consumption. Ayobandung.com special provisions that can be used as guidelines by netizens, and makes a selection of incoming writings. Ayo Bandung from all aspects of the basic principles of citizen journalism found that, in general, the average netizen sends writings that are not plagiarism, accurate, careful, clear, not hoax, balanced and easy to understand, although there are some netizens' writings that are messy, the data is incomplete, not in accordance with facts and data, and even some writings offend SARA.